Machinist - Boraas, Tracey (Mankato, MN : Capstone Books, 2000)
Introduces the career of machinist, including educational requirements, duties, workplace, salary, employment outlook, and possible future positions.
Includes bibliographical references (p. 44) and index.
Keywords: Machinists -- Vocational guidance -- Juvenile literature; Machinists -- Vocational guidance; Vocational guidance